2009
DOI: 10.1002/pen.21603
|View full text |Cite
|
Sign up to set email alerts
|

Effects of coagulation bath temperature and polyvinylpyrrolidone content on flat sheet asymmetric polyethersulfone membranes

Abstract: In this study, effects of coagulation bath temperature (CBT) and polyvinylpyrrolidone (PVP K15) concentration as a pore former hydrophilic additive on morphology and performance of asymmetric polyethersulfone (PES) membranes were investigated. The membranes were prepared from a PES/ethanol/NMP system via phase inversion induced by immersion precipitation in a water coagulation bath. The morphology of prepared membranes was studied by scanning electron microscopy (SEM), contact angle measurements, and mechanica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
46
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(54 citation statements)
references
References 38 publications
7
46
0
1
Order By: Relevance
“…The changes imposed on membrane structure and properties after addition of Brij ® S100 and variation of PES concentrations are major reasons for PWF changes. At first, it should be noted that PWF highly depends on membrane porosity and particularly the thickness and porosity of top layer [24,31]. Above results of PWF are in agreement with trend observed in SEM images.…”
Section: Resultssupporting
confidence: 82%
“…The changes imposed on membrane structure and properties after addition of Brij ® S100 and variation of PES concentrations are major reasons for PWF changes. At first, it should be noted that PWF highly depends on membrane porosity and particularly the thickness and porosity of top layer [24,31]. Above results of PWF are in agreement with trend observed in SEM images.…”
Section: Resultssupporting
confidence: 82%
“…Such amounts of PVP are known to alter the phase inversion process and have a notable influence on the membrane morphology, e.g. as a macrovoid suppressor (high MW) and a pore former (low MW) [30][31][32]. Specifically, for polyimide membranes, Yoo et al showed that PVP (40 kDa) influenced the thermodynamical behavior of the casting solution and the rate of solvent exchange during phase inversion and that PVP suppressed …”
Section: Effect Of Gnps On Membrane Structurementioning
confidence: 97%
“…Saljoughi and co-workers [2] studied the effect of coagulation bath temperature on polymeric membranes. They discovered that increasing coagulation bath temperature increases permeability and decreases rejection.…”
Section: Introductionmentioning
confidence: 99%
“…The phase inversion method can be accomplished by a wide variety of techniques such as non-solvent induced phase separation, vapor induced phase separation, thermally induced phase separation and evaporation induced phase separation [1,2]. The non-solvent induced phase separation process is without a doubt the most widely used technique for preparation of polymeric hollow fiber membranes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation